## Trending News

Promoted

# What would you like to ask?help me figure out this ^-2 equation. i always get stuck on this?

a^-2 + b^-2 / a^2 + b^2

help me i jut dont understand this,, working out if possible

### 2 Answers

Relevance

- jcherry_99Lv 79 years agoFavorite Answer
Please put brackets around what you mean.

I think your question is (a^-2 + b^-2) / (a^2 + b^2) Am I right? If not put something under additional information.

(1/a^2 + 1/b^2) / (a^2 + b^2)

Now consider 1/a^2 + 1/b^2 by itself.

(a^2 + b^2) / a^2 * b^2 is what you get when you add these two together.

(a^2 + b^2)/[(a^2*b^2)*(a^2 + b^2) ] I'll write this in a slightly more understandable way.

(a^2 + b^2)

========

(a^2*b^2)*(a^2 + b^2) The a^2 + b^2 cancel out

1/(a^2*b^2)

- 9 years ago
assuming it is

(a^(-Â²) +b^-Â²) /( aÂ²+bÂ²) =

(1/a+1/b) /( aÂ²+bÂ²) =

(b+a)/ ab /( aÂ²+bÂ²) =

(b+a) /ab( aÂ²+bÂ²)

Still have questions? Get your answers by asking now.